2014
DOI: 10.15296/ijwhr.2014.08
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Laparoscopy in the Evaluation of Female Factors in Infertility in Kashmir Valley

Abstract: Objectives: To evaluate the female factors in infertility using laparoscopy in Kashmiri women. Materials and Methods: One hundred cases of infertility [primary and secondary] were included in this prospective study. Before the procedure, apart from complete history and detailed examination, baseline investigations (complete blood count, blood sugar, kidney and liver function tests, ECG, chest X-ray) were performed as per our institutional protocol for pre-anaesthesia check up. Laparoscopy was done in prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…It was comparable with studies conducted by Nayak KP et al, Shetty KS et al, Vaid K et al and Shah JS et al [7][8][9][10][11] Present study revealed abnormal laparoscopic findings in 73% patients and abnormal hysteroscopic findings in 47% patients. Forty% (40) patients had abnormal findings on laparoscopy alone and 14 (14%) patients had abnormal findings on hysteroscopy alone which was similar to the study conducted by Singh R et al 9 Mean age of patients with primary infertility was 28.6±4.20 years and with secondary infertility was 32.1±3.84 years (34%) that was comparable to the studies conducted by Shetty KS et al, Wani Q et al and Chimote A et al 8,12,13 In present study, uterine myoma was the most common abnormality found on hysteroscopy similar to Shah JS et al (8%), depicting that myomas influence infertility. 40% patients had only abnormal laparoscopic findings while 33% of patients had abnormalities on both hysteroscopy and laparoscopy resulting in total of abnormal findings in 73% patients.…”
Section: Discussionsupporting
confidence: 82%
“…It was comparable with studies conducted by Nayak KP et al, Shetty KS et al, Vaid K et al and Shah JS et al [7][8][9][10][11] Present study revealed abnormal laparoscopic findings in 73% patients and abnormal hysteroscopic findings in 47% patients. Forty% (40) patients had abnormal findings on laparoscopy alone and 14 (14%) patients had abnormal findings on hysteroscopy alone which was similar to the study conducted by Singh R et al 9 Mean age of patients with primary infertility was 28.6±4.20 years and with secondary infertility was 32.1±3.84 years (34%) that was comparable to the studies conducted by Shetty KS et al, Wani Q et al and Chimote A et al 8,12,13 In present study, uterine myoma was the most common abnormality found on hysteroscopy similar to Shah JS et al (8%), depicting that myomas influence infertility. 40% patients had only abnormal laparoscopic findings while 33% of patients had abnormalities on both hysteroscopy and laparoscopy resulting in total of abnormal findings in 73% patients.…”
Section: Discussionsupporting
confidence: 82%
“…The World Health organization (WHO) estimates that 60 to 80 million couples worldwide currently suffer from infertility. Infertility varies across regions of the world and is estimated to affect 8 to 12 percent of couples worldwide 6 .…”
Section: Discussionmentioning
confidence: 99%
“…A single episode of PID carries upto 10 % risk of future tubal factor infertility 6 . In our study PID, hydrosalphinx, TO mass were present in 5.15% and 7.59% in primary and secondary infertility respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is considered as an important tool not only in diagnosis of infertility but also in the treatment of selected cases. 8 In the present study, an effort was made to establish the role of laparoscopy in primary and secondary infertility cases in women and to detect the diagnostic efficacy of laparoscopy in uterine, pelvic and ovarian pathologies.…”
Section: Introductionmentioning
confidence: 99%